Role of Pathology in Animal Disease Diagnosis from Antiquity to Modernity - Singh, Rajendra; Somvanshi, R.; Singh, S. D. (Indian Farming, 2015)
Pathological diagnosis of animal diseases has been the forte of scientists of the Division of Veterinary Pathology at IVRI, since the very begining. In its long journey of Patho-diagnosis since its establishment, it has come a long way and still plays a very important role in the prognosis and diagnosis of various problems faced by the livestock, poultry and wildlife with respect to their diseases.